THE IMPACT OF NEW CAR MARKET ON THE DKI JAKARTA POLICY TO LIMIT THE NUMBER OF VEHICLES - Hakoso, Mego Widi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
A considerably high consumption of cars has led Jakarta to such a messy traffic that prompted the need for the DKI Jakarta Government to issue policies to fetter the public’s purchase power for new cars. Despite this, the public continues to buy new cars. This research was conducted using qualitative method, and also post-positivism paradigm as a viewpoint from which the field arena is observed. Data collection was done by conducting a review on documents, printed – online media news and interviews from various sources. Honda Brand, which is notably the market leader in Jakarta, is to be a representative of how business players address the DKI Jakarta Government’s policy which intends to reduce the purchase power. The result of this research shows that traffic jam in Jakarta has been a complex problem politically since the New Order, because automotive business players, as a capital, have become part of Indonesia’s political power and the performance of Honda Mobil sales has not been affected by the DKI Jakarta Government’s policy in holding back the public’s purchase power for new cars. Key Words: Automotive, Policy, Jakarta, Market, Honda